The Political Fourth Amendment - Thomas P. Crocker (Washington University Law Review, 2010)
The Political Fourth Amendment builds on Justice Ginsburg's recent dissent in Herring v. United States to argue for a “more majestic conception” of the Fourth Amendment focused on protecting political liberty. To put the point dramatically, we misread the Fourth Amendment when we read it exclusively as a criminal procedure provision focused entirely on either regulating police or protecting privacy. In order to see the Fourth Amendment as contributing to the Constitution's protections for political liberty, and not simply as an invitation to regulate police practice, we must take seriously the fact that the Fourth Amendment's textual purpose is to secure a “right of the people,” which places it textually alongside the First, Second, and Ninth Amendments that similarly seek to protect the “right[s] of the people.” Narratives focused on regulating police or protecting privacy each risk blinding us to the Fourth Amendment's broader constitutional setting. By looking at the historical origins of the Fourth Amendment in relation to substantive First Amendment concerns, and examining the textual significance of protecting a “right of the people,” this Article argues that the two dominant narratives overlook a central political purpose of the Fourth Amendment. The political Fourth Amendment seeks to protect the political liberties of the sovereign “People.” Focused exclusively on protecting privacy by regulating police practice, current Fourth Amendment doctrine offers no protection to anything a person knowingly exposes to others, a hazard in an era of electronic social networking. Reading the Fourth Amendment back into the Constitution makes available new grounds for the Constitution's relevance in an age of pervasive electronic surveillance.
Keywords: Searches & seizures (Law); Electronic surveillance; Right of privacy; Sedition; Libel & slander; Constitutional law; Liberty